Diagnosis from the Communicative Competences on the Learning of the English language of the Students of the Don Bosco Center Industrial Technical Institute (Papeles, 2017)
The study refers to the learning of the English language for specific purposes, a process in which the development of a specific communicative competence proper to the know-how of a specific area of knowledge, is strengthened. Its objective was to determine, through participant observation and a self-applied questionnaire, the specific communicative competences for the learning of English that the students of the technical training programs for work and human development of the Don Bosco Center Industrial Technical Institute need to develop. His approach was mixed. Both its results and its discussion call for proposals that focus on establishing specific teaching strategies to strengthen the taste and skills of reading, writing and speaking in English for specific purposes.
Keywords: learning English; education for work and human development; communicative competences; didactic strategies; interpretation of technical documents